ACCOUNTING AND THE S.E.C. (The Accounting Review, 1938)
Abstract The article presents four additional cases supplied by the U.S. Securities and Exchange Commission as illustrative of the questions raised with public accountants on annual financial statements. In each instance the question has been resolved by acceptance of the recommendations by the Commission's staff. The solutions of the problems raised are not necessarily precedents which the Commission's staff is obligated to follow in the future, but they are without doubt shaping accounting theory into new molds. It is of interest to observe in a case that despite an existing deficit from operations, the Commission has insisted that a write-off of assets be added to such deficit rather than be charged to paid-in surplus. This is a position consistent with the practice of many accountants and with the Association's tentative statement of principles. Attorneys who still insist that an operating deficit dissociated from capital is unthinkable, in view of the fact that it represents a loss of assets, would do well to review the Commission's attitude on the subject. In effect, that attitude has been to regard the detail of net worth as a historical record in which the distinctions between contributed and accumulated capital must be preserved for the information of investors and others until, by formal consent of the stockholders, their contributions have been reduced to the net-asset level reflected in the balance sheet.